2022
DOI: 10.1186/s12889-022-14557-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with insomnia and suicidal thoughts among outpatients, healthcare workers, and the general population in Taiwan during COVID-19 pandemic: a cross-sectional study

Abstract: Background Insomnia and suicidal thoughts are two of the negative impacts that have been caused by the COVID-19 pandemic. Identifying the factors that contribute to these psychological problems may help develop strategies to sustain the mental health of the public. The present study examined the psychosocial impacts caused by the COVID-19 pandemic among different populations in Taiwan, and investigated the relationships between these psychosocial variables, insomnia, and suicidal thoughts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
3
6
0
Order By: Relevance
“…Another finding in this study indicated that a severe or moderate level of fear of Covid-19, when added alongside the pandemic year in the logistic regression model, increased the probability of being in the group with suicidal ideation. Initially, the data found in this study confirmed the literature by suggesting that a greater fear of Covid-19 appears to be associated with suicidal behaviors [19] [20]. Other studies found that fear can have detrimental effects when it persists and intensifies [17] [49] [18], as is the case with the Covid-19 pandemic, which resulted in prolonged exposure to the fear of infection and the presentation of severe forms of the disease.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Another finding in this study indicated that a severe or moderate level of fear of Covid-19, when added alongside the pandemic year in the logistic regression model, increased the probability of being in the group with suicidal ideation. Initially, the data found in this study confirmed the literature by suggesting that a greater fear of Covid-19 appears to be associated with suicidal behaviors [19] [20]. Other studies found that fear can have detrimental effects when it persists and intensifies [17] [49] [18], as is the case with the Covid-19 pandemic, which resulted in prolonged exposure to the fear of infection and the presentation of severe forms of the disease.…”
Section: Discussionsupporting
confidence: 85%
“…Even with exposure, it is important to understand how capable, skilled, or confident a person feels in dealing with the fear-inducing event. For example, a higher level of fear of Covid-19 has been associated with a higher likelihood of exhibiting suicidal behavior in Taiwan and Spain [19] [20], as well as symptoms of anxiety and depression [17] as evidenced in a systematic review conducted in over 30 countries.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study resonate with our recent findings in Taiwan, as reported in BMC Public Health , 2 where we investigated the factors contributing to insomnia and suicidal thoughts among different populations during the COVID-19 pandemic. We found that greater fear of COVID-19 was significantly associated with suicidal thoughts across outpatients, health-care workers, and the general population.…”
supporting
confidence: 91%
“…Resilience is not a linear path toward happiness, but a combination of behaviors that encourages individuals and communities to persevere and move forward confronting difficult situations ( 24 , 25 ). Higher level of resilience might decrease the risk of developing psychological distress, and suppress suicidal thoughts and insomnia ( 26 , 27 ). Resilience might be influenced by job stress, perceived stress, and mindfulness, and be promoted by brief resilience interventions based on positive psychology ( 28–30 ).…”
Section: Introductionmentioning
confidence: 99%